Prioritisation of barriers for supply chain management implementation in the Malaysian automotive industry - Anis, Azilah; Islam, Rafikul; Hafit, Nor Intan Adha (Associacao Brasileira de Engenharia de Producao, 2022)
Paper Aim: Several Barriers impede the robust effectiveness of the supply-chain management implementation for the Malaysian automotive industry. The purpose of the present work is to identify these Barriers and prioritize them. Originality: Originality of the present work lies in identifying the Barriers, putting them into categories and subsequently prioritize them by applying a scientific method such as Analytic Hierarchy Process (AHP).